2022
DOI: 10.1177/11206721221126301
|View full text |Cite
|
Sign up to set email alerts
|

Premium intraocular lenses in children

Abstract: Multifocal and toric intraocular lenses (IOLs) or the so-called premium IOLs are currently widely used in adult patients as a one-step refractive solution following cataract surgery. However, the decision to implant a premium IOL in a pediatric patient involves multiple factors affecting the child’s visual development and is associated with several dilemmas and surgical challenges. The purpose of this review is to summarize these factors and analyse the influence of each of them on the visual outcomes followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…There are few studies on multifocal IOLs in pediatric patients. The most recent systematic review [21] found only case reports and smaller interventional trials, and though refractive outcomes were generally good, there was not enough data to be conclusive. There was also internal variation within the included reports.…”
Section: Multifocal Intraocular Lensesmentioning
confidence: 99%
“…There are few studies on multifocal IOLs in pediatric patients. The most recent systematic review [21] found only case reports and smaller interventional trials, and though refractive outcomes were generally good, there was not enough data to be conclusive. There was also internal variation within the included reports.…”
Section: Multifocal Intraocular Lensesmentioning
confidence: 99%